OA21 The power to choose: developing community capacity to provide palliative care in four first nations communities in canada. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Kelley, Mary Lou; Prince, Holly; Monture, Lori; Maki, Luanne; Crow, Maxine; Smith, Jeroline
Abstract : Background: First Nations people in Canada are ageing with a high burden of chronic, progressive, and life-limiting illness. The majority now die in urban hospitals or long term care homes far away from family and culture. Today, First Nations community leaders are working to build local community capacity to support people and their families who choose to die at home. Aim: This presentation describes a five year participatory action research project that has enhanced local palliative care capacity in four First Nations communities using innovative strategies for collaboration, education, and advocacy (www.eolfn.lakeheadu.ca ). Methods: The process of community capacity development was locally driven and controlled. A local leader and advisory committee implemented a palliative care community assessment that identified resources and needs for community awareness, health provider education, service development and improved partnerships with external health care providers (physicians, hospitals etc) providing care to community members. Innovative strategies to address these needs were developed, implemented and evaluated. Results: If services and community supports were available, 87% of the FN community participants would prefer to die at home. Each of the four participating FN communities developed a unique palliative care program model responsive to community culture and context. Culturally appropriate videos and print resources for education and community development were created to share internationally. Conclusion: First Nations communities have the desire and capacity to care for community members to the end of their lives. Community development and advocacy are required to support First Nations in addressing existing barriers and gaps in education, policy and service delivery.